2019
DOI: 10.3233/jad-180975
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Informant-Reported Functional Performance in Mild Cognitive Impairment: A Latent Profile Analysis of the Functional Activities Questionnaire

Abstract: Heterogeneity of subtle functional difficulties in mild cognitive impairment (MCI) remains poorly understood. We characterized patterns of informant reports of functional abilities among participants with MCI and the relation between functional ability pattern and cognitive abilities and subsequent decline. Data from 4,273 MCI participants from the National Alzheimer's Coordinating Center (NACC) Uniform Data Set (UDS) were included in latent profile analyses (LPA) of informant responses on the Functional Activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…These findings differ from what is established by the diagnostic criteria for mdMCI. The present results, together with those of previous studies (Kaur, Belchior, Gelinas, & Bier, 2016;Mis, Devlin, Drabick, & Giovannetti, 2019;Rodríguez-Bailón et al, 2015, show the need to pay special attention to the evaluation of subtle cognitive processes involved in everyday tasks. The contribution of our study to the existing knowledge about the cognitive-functional deficits that characterize patients with mdMCI and dementia in initial stages can help in the early diagnosis of this population using a quick and simple tool that can assess patients in their everyday contexts.…”
Section: Discussionsupporting
confidence: 84%
“…These findings differ from what is established by the diagnostic criteria for mdMCI. The present results, together with those of previous studies (Kaur, Belchior, Gelinas, & Bier, 2016;Mis, Devlin, Drabick, & Giovannetti, 2019;Rodríguez-Bailón et al, 2015, show the need to pay special attention to the evaluation of subtle cognitive processes involved in everyday tasks. The contribution of our study to the existing knowledge about the cognitive-functional deficits that characterize patients with mdMCI and dementia in initial stages can help in the early diagnosis of this population using a quick and simple tool that can assess patients in their everyday contexts.…”
Section: Discussionsupporting
confidence: 84%
“…That is, according to current clinical diagnostic criteria, individuals with the exact same cognitive test scores may be diagnosed with either mild dementia or MCI depending on their level of functional ability. Further, it has been shown that even small differences in the FAQ can have a robust threshold effect, such that any increase over 1 point on the FAQ sum is associated with a threefold increased risk of conversion from MCI to dementia (Mis, Devlin, Drabick, & Giovannetti, 2019) and a significantly greater risk of conversion to either MCI or dementia in healthy controls (Nowrangi, Rosenberg, & Leoutsakos, 2016). Therefore, even small effects of informant features, such as the modest effect sizes observed in this study (.008 < η p 2 's ≤ .033), may have a meaningful impact on predictive validity of the FAQ.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was once thought that the familiarity and frequency of everyday tasks made them impervious to mild cognitive difficulties, empirical research shows that even relatively simple and highly familiar everyday activities are negatively affected by distraction and subtle cognitive changes or decline (Tucker-Drob, 2011). In fact, in healthy older adults and older adults with MCI, mild functional difficulties are associated with cognitive abilities/deficits (Beaver et al, 2019; Black & Rush, 2002; Colón-Emeric et al, 2013; Freedman et al, 2002) and predict subsequent cognitive decline and dementia (Gomar et al, 2011; Farias et al, 2018; Mis et al, 2019; Tucker-Drob, 2011).…”
Section: Future Directionsmentioning
confidence: 99%